Proton dynamics in phosphotungstic acid impregnated mesoporous silica proton exchange membrane materials - Lamb, K.; Mole, R.; Yu, D.; De Marco, Roland; Bartlett, J.; Windsor, S.; Jiang, San Ping; Zhang, J.; Peterson, V. (2017)
Phosphotungstic acid is an excellent proton conductor that can be incorporated into porous supports, and nanocomposite proton exchange membrane materials made from mesoporous silica impregnated with phosphotungstic acid have been suggested for use in fuels cells operating > 100 °C. In this work, quasielastic neutron scattering was used to study proton self-diffusion in mesoporous disordered and P6mm symmetry silica impregnated with two concentrations of phosphotungstic acid. Overall, the silica structure had a significantly greater effect on proton conduction and diffusion than phosphotungstic acid concentration, with higher proton conduction occurring for the P6mm symmetry silica samples. Quasielastic neutron scattering revealed two populations of protons diffusing through each sample, and that proton conduction is limited by the slower of these populations, which diffuse via a jump-diffusion mechanism. Whilst the fundamental jump-diffusion mechanism by which these slower protons moved was found to be similar for both silica supports and phosphotungstic acid concentrations, the faster diffusion occurring in P6mm structured silica arises from a lower residence time of protons moving between sites in the jump-diffusion model, suggesting a lower energy barrier.